INVESTIGATION OF SPECTRAL AND OPTICAL PROPERTIES OF SOME ORGANIC EYEGLASS LENSES - Ateş, Gonca; Bilici, Sevim (Inonu University, 2023)
In this study, the spectral and optical properties of organic spectacle lenses used as visual aids were analyzed using Jasco V-730 UV/VIS spectrophotometer device in the ultraviolet and visible light wavelength ranges. The results obtained showed that the light transmittance in the wavelength (550nm) range to which the human eye is most sensitive in the lens samples examined was over 80% and that Polycarbonate (A3) lenses had a maximum value of 97.87%. The largest cut-off edge wavelength value was found to be 390nm for the A3 lens. At 550 nm for all lenses, the absorption spectrum was below 0.07. In terms of visual quality, it is expected that the visible light transmittance is high and the ultraviolet light transmission is minimal. Our eyes are exposed to ultraviolet rays almost every day, and these rays cause damage to the ocular tissues. The degree of damage caused by the amount of ultraviolet light absorption increases. Among the organic lenses with ultraviolet protection coating, the protection of the A3 lens was relatively higher. Furthermore, optical band gap energies were found to range from 3.145 – 4.155 eV and 2.994 – 3.936 eV for direct and indirect transitions, respectively. The highest optical band gap values were found to be those of the B1 and C1 organic lenses, respectively. © 2023, Inonu University. All rights reserved.
Bazı Organik Gözlük Camlarının Spektral ve Optik Özelliklerinin İncelenmesi
Keywords: CR-39 lens; Eye health; Polycarbonate lens; UV radiation